“Покаяльний” лист поета Миколи Данька - Артюх, В.О.; Садiвничий, В.О. (Сумський історико-архівний журнал, 2010)
Two variants of the “penitential letter” by the poet, publicist, recusant Mykola Danko
are given in the article. The first variant was written by the author himself. Nowadays it is
stored at Sumy Region State Archive and it should be mentioned the document is published
for the first time. The second one was published in “Leninska Pravda” newspaper. According
to Mykola Danko it had been prepared for publication by the journalist of the newspaper
under the supervision of KGB officers.